2008
DOI: 10.1007/s10529-008-9666-9
|View full text |Cite
|
Sign up to set email alerts
|

Accumulation of cell wall-bound phenolic metabolites and their upliftment in hairy root cultures of tomato (Lycopersicon esculentum Mill.)

Abstract: Alkaline hydrolysis of cell wall material of tomato hairy roots yielded ferulic acid as the major phenolic compound. Other phenolics were 4-hydroxybenzoic acid, vanillic acid, 4-hydroxybenzaldehyde, vanillin and 4-coumaric acid. The content of phenolics was much higher at the early stage of hairy root growth. The ferulic acid content decreased up to 30 days and then sharply increased to 360 microg/g at 60 days of growth. Elicitation of hairy root cultures with Fusarium mat extract (FME) increased ferulic acid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 20 publications
(18 reference statements)
1
21
0
Order By: Relevance
“…The results obtained in this study resemble those reported earlier from our laboratory in respect to detection and analysis of CWB phenolic compounds in coconut mesocarp (Dey et al 2005). The results of this study are also highly consistent with a report on accumulation of CWB phenolic compounds in hairy roots of tomato on a time course basis (Mandal and Mitra 2008). Similar studies carried out in date palm confirmed the presence of four CWB phenolics, namely 4-hydroxybenzoic acid, 4-coumaric acid, ferulic acid and sinapic acid in the root organs of the plant.…”
Section: Discussionsupporting
confidence: 92%
“…The results obtained in this study resemble those reported earlier from our laboratory in respect to detection and analysis of CWB phenolic compounds in coconut mesocarp (Dey et al 2005). The results of this study are also highly consistent with a report on accumulation of CWB phenolic compounds in hairy roots of tomato on a time course basis (Mandal and Mitra 2008). Similar studies carried out in date palm confirmed the presence of four CWB phenolics, namely 4-hydroxybenzoic acid, 4-coumaric acid, ferulic acid and sinapic acid in the root organs of the plant.…”
Section: Discussionsupporting
confidence: 92%
“…Although the HCA concentrations required for growth inhibition in vitro are 10 to 100-fold higher than concentrations measured in planta , concentrations of these compounds in the xylem of roots and stems may be locally high where phenolics are released by sentinel phenolic-storing-cells (Beckman, 2000; Alvarez et al, 2008; Mandal and Mitra, 2008; Wallis and Chen, 2012). Additionally, the metabolic state of R. solanacearum cells affected their susceptibility to HCAs; HCAs were more inhibitory when R. solanacearum was grown in glucose minimal media than when grown in succinate minimal media (data not shown).…”
Section: Discussionmentioning
confidence: 96%
“…Roots exude HCAs and related phenolics to chelate metals, thereby facilitating uptake and transport of metals in the xylem sap (Ishimaru et al, 2011). In response to root pathogens, many plants release de novo synthesized HCAs into the rhizosphere, and grapevines infected with Xylella accumulate HCAs and HCA-conjugates in their xylem sap (Mandal and Mitra, 2008; Lanoue et al, 2010; Wallis and Chen, 2012). HCAs are broadly antimicrobial; they disrupt membrane integrity and decouple the respiratory proton gradient (Fitzgerald et al, 2004; Harris et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous reports had already proven that other plant species can also produce phenolic compounds such as alkaline hydrolysis of cell wall material. Tomato hairy roots yielded ferulic acid as the major phenolic compound (Mandal and Mitra 2008). Sircar et al 2007 reported the accumulation of p-hydroxybenzoic acid in Agrobacterium rhizogenes-induced hairy root cultures of Daucus carota.…”
Section: Discussionmentioning
confidence: 99%